Effects of waste glass particle size on improving the property and environmental safety of fired brick containing electroplating sludge. (10th October 2020) - Mao, Linqiang; Zhou, Huan; Peng, Mingguo; Hu, Linchao; Zhang, Wenyi
Graphical abstract: Highlights: Larger diameter waste glass improve brick properties more effectively. Larger diameter waste glass was easy to form molten glass–ceramic phase. Smaller particle size waste glass tends to form crystalline quartz. Larger diameter waste glass decreases environmental safety of brick. Abstract: The introduction of industrial solid waste in fired clay brick is a promising way to consume this waste, however, physical and mechanical properties were seriously impacted due to the incorporation of these solid waste. In current study, various particle diameters of waste glass powder (WGP) were introduced in the preparation process of brick to examine the difference in improving physical and mechanical performances of products, and to obtain the optimal particle size of waste glass for applying in the preparation of fired brick. Results showed the incorporation of WGP in larger particle size (100 and 300 meshes) can effectively improve properties, like bulk density, water absorption and compressive strength, but decrease thermal conductivity slightly. XRD and SEM analysis revealed that WGP with particles size of 100 and 300 meshes would become glass–ceramic phase or form albite, which can improve effectively physical and mechanical properties. However, part of WGP with particle size of 600 and 800 meshes might melt and crystalize into quartz at high temperature. The addition of WGP in particle size of 100 and 300 meshes can decrease much leachability of heavy metals from fired bricks and promote environment safety comparing with WGP with particle size of 600 and 800 meshes. Above results suggested that there is no necessary to grind WGP in much smaller particle size during introduction of waste glass for improving fired brick property. The conclusions from this research give some useful information for the incorporation of WGP in the preparation of fired brick.